Comparison of the Influence of Two Flap Designs on Periodontal Healing after Surgical Extraction of Impacted Third Molars - Seyed Ahmad Arta; Reza Pourabbas Kheyradin; Ali Hossein Mesgarzadeh; Bahador Hassanbaglu (Tabriz University of Medical Sciences, 2011)
Background and aims. Impacted lower third molar is found in 90% of the general population. Impacted lower third molar surgery may result in periodontal complications on the distal surface of the adjacent second molar. The aim of this study was to evaluate the effect of flap design on the periodontal status of the second molar after lower third molar surgery. Materials and methods. Twenty patients, with an age range of 18-26 years, participated in the present study. The inclusion criteria consisted of the presence of bilateral symmetrical impacted third molars on panoramic radiographs. The subjects were randomly divided into two groups. The impactions on the left and right sides were operated by Szmyd and triangular flaps, respectively. Postoperative management and medications were similar for both groups. The subjects were evaluated at two-week, one-month, and six-month postoperative intervals by a surgeon who was blind to the results. Data was analyzed by t-test using SPSS 11 software. Results. There were no significant differences in clinical attachment loss, pocket depth, bone level, plaque index, and free gingival margin between the two flaps (p>0.05). Conclusion. The results of the present study did not show any differences in pocket depth, clinical attachment level, bone level and FGM (free gingival margin) between the two flap designs under study.